Pelayanan dan Rehabilitasi Sosial terhadap Gelandangan dan Pengemis di Panti Sosial Bina Karya Pangudi Luhur Bekasi - Ruaida Murni (Jurnal Penelitian Kesejahteraan Sosial, 2014)
This case study is to describe the sevice and rehabilitation process done by PSKBKPL, on advanced education, understand institution apparatus, advanced education implementation, and supporting and handicap factors. The researchresult hoped can give an input to the Directory of Social Handicap Service to set a policy on service and rehabilitation implementation for homeless and beggar on advanced education done by PSBKPL. This research is evaluation with qualitative technique. The result shows that service and rehabilitation process by PSBKPL based on guidance made by the Directory of Social Handicap Service, because there is unadequate understanding between advanced education andevaluation-monitoring (Monev), caused advanced education and monev are done at the same time and place. Advanced education output shows that economically the lives of ex-educated members majority are still hand-to-mouth conDirektoration, but the change of attitude showed through working effort and their spirit to enhance it for not to be back in homeless and beggar. Only small numbers of ex-educated, with several reasons, back in conDirektoration they used to be. Handicap that felt by apparatus is that the issue has not been thought proporsionally, such as fund limitation, has not special guidance,there has not been yet role from the sending institution and community, and there is no advanced assistance to develop enterpreneurship, that causes ex-social educated are not be able to develop as maximum.